ANALISIS KEBUTUHAN PENGEMBANGAN KEPROFESIAN GURU SMP NEGERI 1 PONTIANAK MELALUI PENILAIAN DIRI - Yuniarti, Yuyun (Universitas Tanjungpura, 2021)
AbstractÂ This research is a survey research to determine teacher professional development programs that can be carried out by schools through teacher self-assessment. The results of this study can be used to determine professional development programs that can be carried out by schools based on self-assessment according to the needs of teachers. The self-assessment carried out by the teacher to analyze the need for Teacher Professional Development is carried out with a questionnaire that includes a person's strengths and weaknesses, Desired or required Career or Professional Development and the reasons for choosing the career development. Based on the survey, it can be seen that there is a comparison between the strengths of teachers and their weaknesses for the four competencies that teachers must have, it is also in accordance with the professional development program needed to improve the four competencies of teachers.Â Keywords: Self-Assessment, Teacher Professional Development